A Comment on "Measuring Monetary Policy in the Euro Area Using SVARs with Residual Restrictions" - Ryan D. Ratcliff (Institute for Replication (I4R), 2024)
Badinger and Schiman (2023) use a narrative high-frequency analysis of news and financial markets to develop a small set of restrictions on the structural shocks of a VAR of the Euro area. Their approach does not uniquely identify a structural representation, so their results are based on the distribution of a randomly generated set of parameters that satisfies the restrictions. Their method generates impulse responses that are consistent with macroeconomic theory, but that differ from previous studies that use alternative highfrequency identification strategies. They use this difference to argue that, unlike previous studies, their method is able to separate monetary policy surprises from confounding central bank information shocks - an important new contribution to the literature. I conducted two replication studies of their work on behalf of the Institute for Replication (I4R). First, I used the code provided in their replication package to replicate all of their main results, aside from the small variations expected in replicating a Monte Carlo study. Second, I attempted to use their original data to recreate their results using a different statistical software (Eviews 13). I was unable to replicate their results for two reasons. First, my program is unable to exactly replicate the custom prior they used to generate their reduced-form results. Second, my models routinely generated nonstationary VARs that nevertheless satisfied the identification restrictions. This differs from the author's results, but is not surprising given the ambiguous stationarity of the underlying macro variables.
Keywords: C32; E43; E44; E52; E58; 330; Structural VAR; Residual Sign Restrictions; Replication